The Effect of Administration Platycerium bifurcatum (Cav.) C.Chr Extract on Total Bilirubin Levels and Hepatosomatic Index Values of Ethanol-Induced Rats - Hendri Saputra; Reza Pertiwi; Delia Komala Sari; Septi Wulandari; Reza Rahmawati (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
The Liver is a vital metabolic organ. Liver injury is related to an inflammatory process that increases the hepatosomatic index (HSI). One indicator of liver damage is increased total bilirubin levels (hyperbilirubinemia). Currently, hyperbilirubinemia treatment is still limited to irradiation therapy and exchange transfusions, because there is no pharmacological specific treatment. This study aimed to evaluate the hepatoprotective effect of Platycerium bifurcatum (Cav.) C.Chr extract on total bilirubin levels and the hepatosomatic index (HSI) in male white rats. A laboratory-based experimental design was employed using a post-test only control group, involving 35 rats randomly assigned to seven groups: normal control, negative control, positive control (sacatonic active), solvent control (Na CMC), and treatment groups receiving ethanol extract at doses of 50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW.The treatment was administered orally for 14 consecutive days. On the final day, all rats (except the normal group) were induced with absolute ethanol at 2 mL/200 gBW. After 12 hours, the animals were euthanized for liver and blood sample collection. Total bilirubin levels were measured, and the hepatosomatic index was calculated. Data were analyzed using one-way ANOVA followed by LSD post hoc test. The results demonstrated that administration of Platycerium bifurcatum (Cav.) C.Chr extract significantly reduced total bilirubin levels and HSI, particularly at doses of 50 mg/kgBW and 100 mg/kgBW, compared to the negative control group (p<0.05). These findings suggest that Platycerium bifurcatum (Cav.) C.Chr ethanol extract exhibits a hepatoprotective effect by reducing total bilirubin levels and HIS.